Zero-Sequence Current Control for Open-End Winding IPMSM Fed by Dual Inverter with a Common Source - Jang, Sung Jin; Hwang, Jun Ho; Lee, Hyung Woo; Lee, Kyo Beum (2022 International Power Electronics Conference, IPEC-Himeji 2022-ECCE Asia, 2022)
This paper proposes a zero-sequence current (ZSC) suppression method using a phase locked loop (PLL). A dual inverter with a common power source generates the ZSC compared to other dual inverter. The reason is that common power source is used and ZSC path is formed by switching. In addition, the ZSC is generated by a zero-sequence voltage (ZSV) and the power switches dead time. The ZSC increases the noise of the open-winding motor and the switching loss of the power switches. In the dual inverter with a common power source, the ZSC has to be considered compared to other dual inverter. The proposed method synchronizes the ZSC to the newly created d-axis through the PLL, and reduces the synchronized ZSC through the PI controller. The validity and effectiveness of the proposed method are verified through simulation results.
Keywords: Common source; Current paths; Dead time; Dual inverters; Open-end windings; Power sources; Power-switches; Suppression method; Zero sequence current; Zero sequence voltage